Understanding traditional healer utilisation for hypertension care using the Andersen model: A qualitative study in Mwanza, Tanzania - Radhika Sundararajan; Rinu Alakiu; Matthew Ponticiello; Giselle Birch; Godfrey Kisigo; Elialilia Okello; Robert N. Peck (Global Public Health, 2023)
Hypertension disproportionately affects people living in African countries, where there are many challenges to appropriate diagnosis and treatment, and many people with hypertension utilise traditional healers as their primary source of healthcare. In this study, we sought to understand factors driving healer utilisation among people with hypertension. We conducted 52 semi-structured interviews with traditional healers, patients and healthcare providers in the Mwanza region of Tanzania. We used the Andersen model of healthcare utilisation to organise our findings on factors driving utilisation of traditional healers for hypertension care. Traditional healers routinely provide care to hypertensive patients and are a critical component of the healthcare landscape. However, healers also operate independently of the biomedical healthcare system, and biomedical providers may hold negative perceptions of healers. Further, healers were described as preferential by patients due to the convenient locations of their practices and perceived improvement of hypertension symptoms with traditional treatment. Finally, healers expressed a desire for more formal collaboration with biomedicine to improve patient care. Our findings may guide future interventions in Tanzanian communities and elsewhere where traditional healers may act as partners to allopathic providers and patients in the continuum of hypertension care.